Dilute sulfonic acid post functionalized metal organic framework as a heterogeneous acid catalyst for esterification to produce biodiesel. (15th April 2020) - Liu, Fengsheng; Ma, Xiaoling; Li, Hui; Wang, Yangyang; Cui, Ping; Guo, Min; Yaxin, Helian; Lu, Wanpeng; Zhou, Shoujun; Yu, Mingzhi
Highlights: A green and stable catalyst was prepared by dilute sulphuric acid and MIL-100(Fe). Lewis and Brønsted acid site were detected in MF-SO3 H. MF-SO3 H achieved 95.86% conversion of oleic acid with methanol in esterification. Catalyst reusability is promising for five cycles without obvious activity loss. Abstract: In order to synthesize the efficient heterogeneous acid catalyst for biodiesel production, concentrated sulfuric acid (>18.4 mol/L) is commonly used as sulfonated reagent to anchor sulfonic acid group (SO3 H) on a support. However, large amount of wastewater is generated while the concentrated sulfuric acid removed by washing. In this study, a green and highly stable sulfonated catalyst is prepared by using MIL-100(Fe), which is functionalized by the dilute sulfonic acid. The obtained catalyst is adopted to catalyze the esterification of methanol and oleic acid. Meanwhile, it is characterized by thermogravimetry analysis (TG), X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), pyridine FTIR spectroscopy (Py-FTIR), scanning electron microscope (SEM), Hammett indicator titration and nitrogen adsorption-desorption. The maximum esterification conversion of 95.86% is achieved at molar ratio of methanol to oleic acid of 10, catalyst amount of 8 wt% (referred to oleic acid mass) at 70 °C within 2 h. More importantly, the catalyst could be repeatedly used for six cycles without significant activity loss.